IMPLEMENTATION OF 454 LIFE SCIENCES TECHNOLOGY LABORATORY PRACTICES - N. G. Zinyakov; Ye. V. Ovchinnikova; S. P. Lazareva; A. A. Kozlov; I. A. Chvalas (Ветеринария сегодня)
He article demonstrates possibility of using highly productive pyrophosphate sequencing, also known as 454 Life Sciences technology for investigation of highly variable and understudied infectious viral agents. Genome-wide nucleotide sequences of infectious bronchitis virus, infectious laryngotracheitis virus, fowl adenovirus C, and avian adenoassociated virus were determined. Recombinations in infectious bronchitis genome were identified, structural and point mutations in fowl adenovirus genome were detect ed. Infectious laryngotracheitis virus and avian adeno-associated virus genome structure was characterized.